Ultrasound-Guided Supraclavicular Brachial Plexus Block - M. S. Sinitsin; A. A. Azbarov; M. I. Tsarev; S. I. Apevalov; V. V. Likhvantsev (Общая реаниматология)
Objective: to evaluate the efficiency of cardiotropic therapy in neonates with severe posthypoxic myocardial ischemia and to improve severity rating criteria that would allow a differentiated approach to therapy for this condition. Subjects and methods. The efficiency of cardiotropic therapy was evaluated in 53 newborn infants with posthypoxic myocardial ischemia. Thirty (56.6%) neonates received phosphocreatinine in a dose of 30 mg/kg/day for 3 days as cardiotropic support; 23 (43.4%) babies had riboxine in a dose of 15—20 mg/kg. Results. The use of phosphocreatinine was found to be more effective than that of riboxine and to favor better blood biochemical composition parameters and lower ECG and intracardiac hemodynamic changes, which in turn reduced the time of mechanical ventilation from 11 to 8.25 days and that of administration of dopamine from 8 to 6 days, and its dose from 2 to 5 mg/kg/min. Conclusion. This investigation has led to the conclusion that there is a need for a comprehensive approach to diagnosing postischemic myocardial damages, including not only their clinical picture, but also a set of biochemical markers for ischemia and ECG and EchoCG changes on the 1st, 3rd, and then every 5—7 days and for the concomitant use of cardiotonic (dopamine) and cardiotrophic (phosphocreatinine) therapy; the administration of phosphocreatinine on intensive care unit admission (after prior hypoxia) as early as possible improves neonatal heart performance values. There are positive changes in both ECG and EchoCG and biochemical parameters (LDH, ALT, AST, De Ritis ratio). Key words: posthypoxic myocar-dial ischemia, neonates, phosphocreatinine.